Arrestee survey, 2003-2006 (UK Data Service, 2011)
The Arrestee Survey, 2003-2006, was the first nationally representative survey of drugs and crime among the population of individuals representing arrest events in England and Wales. The survey aimed to provide information on a range of areas within the drugs and crime nexus, including the prevalence of problematic drug misuse among respondents representing arrest events; drug and/or alcohol consumption; availability of drugs; levels of demand (met and/or unmet) for drug and alcohol treatment services among respondents; levels of intravenous drug use among respondents; and gang membership. The objectives of the survey were to provide the following: measurement of the prevalence and change in problematic drug misuse among a sample of individuals representing arrest events in England and Wales, information to allow monitoring of drug use within drug-using groups that are likely to be under-represented in household surveys, individual-level data for the purpose of researching the behavioural links between drug and/or alcohol consumption and criminal offences leading to arrest, a means to estimate the level of demand (met and/or unmet) for treatment services among the problematic drug/alcohol user population, monitoring information on the level of intravenous drug use among arrestees to better inform harm reduction programmes, a means for routine collection of custody suite information for the purpose of analysing arrestee flows and the process of being in custody, and for analysing the characteristics and offending histories of individuals entering the Criminal Justice System (CJS). For the second edition (October 2011), the weight variables (arrfreqw2 and arrfreqw3) have been updated to include weights for the survey years 2005-2006.